ANALYSIS STUDENTS DIFFICULTY IN READING ENGLISH ARTICLE - Devia Mutiara Sari (Jotika English and Education Center, 2023)
English is a foreign language for Indonesians, it is possible that students who study English have difficulty understanding in reading, because of limited understanding, or wrong reading. This research will be conducted at Ninth Grade Students of Junior High School 6 Mandau. This study used purposive sampling because all participants who were allowed to participate were students who had problems in reading English articles.Researchers discovered from the study's findings that a number of factors influence how challenging it is to read English-language publications. Environmental and psychological elements were used by researchers to determine which factor had the most influence. Learning English articles is not easy. Based on the research, there are difficulties that students experience in learning English articles. These are problems with Grammar, Problems with Vocabulary, and Individual Personality. For further research in foreign language learning, it is hoped that this study can be a source of knowledge and/or information to dig deeper into the problems in learning English. Therefore, there will be rich information on how to overcome these problems.